Scrambling for access: availability, accessibility, acceptability and quality of healthcare for lesbian, gay, bisexual and transgender people in South Africa - Alex Müller (BMC, 2017)
Abstract Background Sexual orientation and gender identity are social determinants of health for people identifying as lesbian, gay, bisexual and transgender (LGBT), and health disparities among sexual and gender minority populations are increasingly well understood. Although the South African constitution guarantees sexual and gender minority people the right to non-discrimination and the right to access to healthcare, homo- and transphobia in society abound. Little is known about LGBT people's healthcare experiences in South Africa, but anecdotal evidence suggests significant barriers to accessing care. Using the framework of the UN International Covenant on Economic, Social and Cultural Rights General Comment 14, this study analyses the experiences of LGBT health service users using South African public sector healthcare, including access to HIV counselling, testing and treatment. Methods A qualitative study comprised of 16 semi-structured interviews and two focus group discussions with LGBT health service users, and 14 individual interviews with representatives of LGBT organisations. Data were thematically analysed within the framework of the UN International Covenant on Economic, Social and Cultural Rights General Comment 14, focusing on availability, accessibility, acceptability and quality of care. Results All interviewees reported experiences of discrimination by healthcare providers based on their sexual orientation and/or gender identity. Participants recounted violations of all four elements of the UN General Comment 14: 1) Availability: Lack of public health facilities and services, both for general and LGBT-specific concerns; 2) Accessibility: Healthcare providers' refusal to provide care to LGBT patients; 3) Acceptability: Articulation of moral judgment and disapproval of LGBT patients' identity, and forced subjection of patients to religious practices; 4) Quality: Lack of knowledge about LGBT identities and health needs, leading to poor-quality care. Participants had delayed or avoided seeking healthcare in the past, and none had sought out accountability or complaint mechanisms within the health system. Conclusion Sexual orientation and gender identity are important categories of analysis for health equity, and lead to disparities in all four dimensions of healthcare access as defined by General Comment 14. Discriminatory and prejudicial attitudes by healthcare providers, combined with a lack of competency and knowledge are key reasons for these disparities in South Africa.